Spinal Neuronal GRK2 Contributes to Preventive Effect by Electroacupuncture on Cisplatin-Induced Peripheral Neuropathy in Mice. (January 2022) - Ma, Xue; Chen, Yu; Li, Xiao-Chen; Mi, Wen-Li; Chu, Yu-Xia; Wang, Yan-Qing; Mao-Ying, Qi-Liang
Abstract : BACKGROUND: The main symptoms of chemotherapy-induced peripheral neuropathy (CIPN) include pain and numbness. Neuronal G protein–coupled receptor kinase 2 (GRK2) plays an important role in various pain models. Cisplatin treatment can induce the activation of proinflammatory microglia in spinal cord. The purpose of this study was to investigate the role of spinal neuronal GRK2 in cisplatin-induced CIPN and in the prevention of CIPN by electroacupuncture (EA). METHODS: The pain and sensory deficit behaviors of mice were examined by von Frey test and adhesive removal test. The expression of neuronal GRK2 in the spinal cord is regulated by intraspinal injection of adeno-associated virus (AAV) containing neuron-specific promoters. The protein levels of GRK2, triggering receptor expressed on myeloid cells 2 (TREM2), and DNAX-activating protein of 12 kDa (DAP12) in spinal dorsal horn were detected by Western blot, the density of intraepidermal nerve fibers (IENFs) was detected by immunofluorescence, and microglia activation were evaluated by real-time polymerase chain reaction (PCR). RESULTS: In this study, cisplatin treatment led to the decrease of GRK2 expression in the dorsal horn of spinal cord. Overexpression of neuronal GRK2 in spinal cord by intraspinal injection of an AAV vector expressing GRK2 with human synapsin (hSyn) promotor significantly inhibited the loss of IENFs and alleviated the mechanical pain and sensory deficits induced by cisplatin. Real-time PCR analysis showed that the overexpression of neuronal GRK2 significantly inhibited the messenger RNA (mRNA) upregulation of proinflammatory cytokine interleukin (IL)-1β, IL-6, inducible nitric oxide synthase (iNOS), and M1 microglia marker cluster of differentiation (CD)16 induced by cisplatin. Furthermore, the TREM2 and DAP12, which has been demonstrated to play a role in microglia activation and in the development of CIPN, were also downregulated by overexpression of neuronal GRK2 in this study. Interestingly, preventive treatment with EA completely mimics the effect of overexpression of neuronal GRK2 in the spinal cord in this mouse model of cisplatin-induced CIPN. EA increased GRK2 level in spinal dorsal horn after cisplatin treatment. Intraspinal injection of AAV vector specifically downregulated neuronal GRK2, completely reversed the regulatory effect of EA on CIPN and microglia activation. All these indicated that the neuronal GRK2 mediated microglial activation contributed to the process of CIPN. CONCLUSIONS: Neuronal GRK2 in the spinal cord contributed to the preventive effect of EA on CIPN. The neuronal GRK2 may be a potential target for CIPN intervention.